2020
DOI: 10.3390/s20216345
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches for Activity Recognition and/or Activity Prediction in Locomotion Assistive Devices—A Systematic Review

Abstract: Locomotion assistive devices equipped with a microprocessor can potentially automatically adapt their behavior when the user is transitioning from one locomotion mode to another. Many developments in the field have come from machine learning driven controllers on locomotion assistive devices that recognize/predict the current locomotion mode or the upcoming one. This review synthesizes the machine learning algorithms designed to recognize or to predict a locomotion mode in order to automatically adapt the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 65 publications
4
36
2
Order By: Relevance
“…The following activities were selected, Walking (W), Stair Ascent (SA), Stair Descent (SD), Ramp Ascent (RA), Ramp Descent (RD) and Stopped (S). Labarrière et al identified these as the most commonly investigated and they require no equipment or skill to perform [ 10 ]. The study received ethical approval from the University of Bath Research Ethics Approval Committee for Health (REACH), reference EP 19/20 003 .…”
Section: Materials and Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…The following activities were selected, Walking (W), Stair Ascent (SA), Stair Descent (SD), Ramp Ascent (RA), Ramp Descent (RD) and Stopped (S). Labarrière et al identified these as the most commonly investigated and they require no equipment or skill to perform [ 10 ]. The study received ethical approval from the University of Bath Research Ethics Approval Committee for Health (REACH), reference EP 19/20 003 .…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The tuning of these controllers is time-consuming and requires a highly skilled prosthetist. In the current state of the art for LMR techniques, the focus has been on the use of ML techniques to automate the process of feature selection, output classification, and personalization [ 10 ].…”
Section: Human Gait and Machine-learning Fundamentalsmentioning
confidence: 99%
See 3 more Smart Citations